1990
DOI: 10.1111/j.1749-6632.1990.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Micronutrients in Relation to Immune Functionsa

Abstract: In approaching the clinical significance of micronutrients, particularly in relation to immune functions, several considerations should be kept in mind. Most importantly, it must be recalled that we do not eat individual nutrients; we eat food, which is a combination of nutrients in a myriad of forms. The adequacy of any diet must be viewed in its totality, particularly as recent advances in research have made us increasingly aware of the physiological and medical implications of nutrient-nutrient interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(7 reference statements)
0
1
0
2
Order By: Relevance
“…Os indivíduos idosos ingerem cerca de metade das recomendações dietéticas (RDA) de zinco, quando fazem sua opção alimentar a partir de um cardápio variado 1,7 . Além disso, os idosos com insuficiência cardíaca congestiva e os hipertensos freqüentemente usam fármacos, como o captopril e diuréticos, que aumentam as perdas renais de zinco 20 . Níveis séricos deficitários de zinco em idosos com megaesôfago podem dever-se à disfagia e conseqüente menor ingestão de alimentos ricos em zinco, como carnes e vegetais folhosos .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os indivíduos idosos ingerem cerca de metade das recomendações dietéticas (RDA) de zinco, quando fazem sua opção alimentar a partir de um cardápio variado 1,7 . Além disso, os idosos com insuficiência cardíaca congestiva e os hipertensos freqüentemente usam fármacos, como o captopril e diuréticos, que aumentam as perdas renais de zinco 20 . Níveis séricos deficitários de zinco em idosos com megaesôfago podem dever-se à disfagia e conseqüente menor ingestão de alimentos ricos em zinco, como carnes e vegetais folhosos .…”
Section: Discussionunclassified
“…Dentre as possíveis causas dessa deficiência, podem-se destacar a menor ingestão da vitamina E 25 e a má absorção 20,23 . Vinte e cinco (l 3,2%) idosos apresentaram níveis séricos de vitamina A menores do que 20 mg%, com prevalência maior em portadores de leucoses (100%), hepatopatia crônica (40%), doença pulmonar obstrutiva crônica (40%), neoplasias pulmonares (28,6%) e megaesôfago (28,6%).…”
Section: Discussionunclassified
“…Fisher et al observed that the serum zinc content was 20 % lower after 2 days storage [25]. The main problem in interpretation of serum zinc estimations results on the fact, that only 1 % of body zinc circulate in serum [26]. In addition the pool of serum zinc serve as a high turnover compartment for trace elements.…”
Section: Introductionmentioning
confidence: 99%